Klondikers in flat bottomed boat on Lindeman Lake, British Columbia, 1897. - La Roche, Frank (1897)
Caption on image: ""Leaving head of Lake Linderman for the Klondike. c1897"" ""Leaving head of Lake Linderman for the Klondike. These boats are fully loaded and are leaving for the north. With favorable weather the journey can be made to Dawson City in about two weeks. When the wind is favorable the sail is used; otherwise the boat is rowed the length of Lake Linderman ,six miles, to the rapids. Half way down the lake is the boundry line between Alaska and Canada. The men with the boats were a hardy lot. They encountered hardships, because human intelligence, strength and courage always will encounter hardships in the race for wealth. If the comforts and necessaries of life are absent in the region of the Yukon, so also were they wanting in the early days of California."" (Frank La Roche, En Route to the Klondike, 1898) Klondike Gold Rush. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number